The regulation of third party funding of commercial litigation - Stewart, Malcolm Grant (2016)
Chapter 1 introduces the topic of third party funding of litigation which is a recent phenomenon in academic circles. Few of the existing papers on commercial litigation funding are empirically based and those that are, with one exception, use surveys and interviews to collect data. Within the legal boundaries of litigation funding, economic theory predicts that in perfectly competitive markets consumers control what is supplied, prices cover costs without excessive profits and inefficient producers are eliminated. However reality rarely conforms to prediction, and regulation may be appropriate in the public interest to overcome market failures arising from information asymmetries. The research focus is: ‘How effectively are commercial third party litigation funders governed and/or regulated?’ Chapter 2 proceeds to consider the literature on regulation, it’s applicability to litigation funding and the interests of stakeholders. A major concern is the ability of a litigation funder to pay the costs of a winning defendant. The conclusion reached in Chapter 3 is that litigation funders have too much choice in the way they report and disclose information and what they actually report and disclose is deficient in meeting the needs of investors. In Chapter 4, using single firm event study methodology I discover that the stock exchange market does not always react as predicted to disclosure by litigation funders and consequently the market is not an adequate proxy for a regulator. Chapter 5 extends chapter 3 on the solvency issue and also considers other stakeholder issues e.g. ethical ones which may require regulation. The conclusion reached is that a light touch independent regulator overseen by the legal services board would be appropriate. This work narrows the literature gap for empirically based economic research and augments and extends the existing literature by examining third party funding of heterogeneous high value, low volume cases in contrast to homogenous, low value, high volume cases. It is the first work on the accounting regulation of litigation funding. This work will also assist investors, the judiciary and other stakeholders to better evaluate the risks of this new industry.